A simulation study on the enhancement of the efficiency of GaN-based blue light-emitting diodes at low current density for micro-LED applications. (11th September 2019) - Jia, Xiantao; Zhou, Yugang; Liu, Bin; Lu, Hai; Xie, Zili; Zhang, Rong; Zheng, Youdou
Abstract: We numerically investigated the optical/electrical characteristics of blue light-emitting-diodes (LEDs) and developed some optimization strategies. Our aim is to increase the optical performance of LEDs at low current density (0.02–2 A cm −2 ) for micro-LEDs used in display applications. First, we investigated the effects of quantum well (QW) number in blue In0.225 Ga0.775 N/In0.10 Ga0.90 N LEDs. We found that at low current density LEDs with lower QW number have much higher internal quantum efficiency (IQE) than those with higher QW number. Second, we also numerically investigated the effects of the electron blocking layer, n-side quantum barrier (QB) doping concentration, QB material and QW width with single quantum well (SQW) structure. For SQW LEDs at low current density, the electron injection efficiency was nearly one. In terms of the QB doping concentration, we found that an appropriate n-side QB doping can ensure Shockley-Read-Hall recombination appropriately equal Auger recombination, which ultimately results in high IQE. For QB material, we choose In0.05 Ga0.95 N as QB material to achieve both high IQE and low forward voltage. Regarding the QW width, we found that although LEDs with wide QW had high IQE, there were also two peaks in the electroluminescence (EL) spectrum, thus 3 nm was used as an optimal QW width. The original 5-QW structure showed a lower IQE range from 50 to 80% at the current density range from 0.01 to 2 A cm −2 and a forward voltage of 3.06 V at 1 A cm −2 . In contrast, our optimized LED structure achieved an IQE of 92.3% at the current density range from 0.01 to 2 A cm −2 and a forward voltage of 2.72 V at 1 A/cm 2 .